Active and reactive power sharing and frequency restoration in a distributed power system consisting of two UPS units - Parlak, Koray Sener; Ozdemir, Mehmet; Aydemir, M. Timur (Elsevier Sci Ltd, 2009)
A distributed power system consisting of two uninterrupted power supplies (UPS) is investigated in this paper. Parallel operation of the two sources increases the established power rating of the system. One of the sources can supply the system even when the other system is disconnected due to some faults, and this is an important feature. The control algorithm makes sure that the total load is shared between the supplies in accordance with their rated power levels, and the frequency of the supplies are restored to the rated values after the transitions. As the UPSs operate at an optimum power level, losses and faults due to overloading are prevented. The units safely operate without any means of communication between each other. The focus of the work is on the inverter stages of the UPSs. Simulations performed in Matlab Simulink environment have been verified with experimental work via DS1103 controller card. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Distributed power systems; Power sharing; Load-frequency control; Frequency restoration; Microgrids